Efektivitas Penyampaian Konten Eduwisata Budaya terhadap Pemahaman Siswa Sekolah Menengah Pertama di Museum Sonobudoyo Yogyakarta - Irdana, Nuryuda; Sholikhah, Faizatush (Jurnal Pariwisata Terapan, 2024)
Museums are present in the community as a place to see information and collections about events that occurred in the past. One of the museums that is well known by the public is Sonobudoyo Museum. Sonobudoyo Museum has a very strategic location because it is located in the center of Yogyakarta, which is a cultural city in Indonesia. Museums are closely related to educational tourism. Most junior high school students are in the age range of 12 - 17 years. As adolescents enter this stage, they acquire the ability to think abstractly by manipulating ideas, without dependence on concrete manipulation. The objectives of this research are 1) Knowing the type of educational content contained in the Sonobudoyo Museum. And 2) Knowing the effectiveness of delivering educational content at Sonobudoyo Museum on the understanding of junior high school students. The analytical tool used in this research is the Wilcoxon Test. The material to be analyzed is primary data obtained from direct observation, interviews, and questionnaires. The survey method is used to analyze the second research objective. The approach used is a quantitative approach. The results of the analysis show that the types of educational content available at Sonobudoyo Museum are pre-historic times, traditional children's games, travel and transportation, banquets and events, performing arts, traditional weapons, and clothing and batik. The results of further analysis regarding the effectiveness of the delivery of edu-tourism content at Sonobudoyo Museum on the understanding of junior high school students show that the delivery of edu-tourism content at Sonobudoyo Museum can provide an understanding of pre-historic times, traditional children's games, travel and transportation, banquets and events, performing arts, traditional weapons, and clothing and batik.